A Scientometric Analysis of Studies on the Effects of the Date palm (Phoenix dactylifera) Fruit on Human Health - Tanty Shahrumi Abdul Rahman; Mohd Dzulkhairi Bin Mohd Rani1; Asmalita Binti Syaiful; Muslimah Binti Ithnin; Mohd Khairul Nizam Bin Zainan Nasri; Khairullah Anuar; Asma Abdul Rahman; Mohd Radzniwan A Rashid; Faizul Helmi Addnan; Khairun Nain Nor Aripin (Universiti Sains Islam Malaysia, 2024)
MJoSHT 2019, Volume 3, Issue1